Investigation of Technology Adaptation in the Hospitality Industry in Mandalika Special Economic Zone - Pratama, Aryan Agus; Jumadi, Muhamad; Ramdani, Rizal; Ahmad, Nur Aisya Addina (Target : Jurnal Manajemen Bisnis, 2024)
Mandalika Special Economic Zone (Mandalika SEZ) has been built and developed to create an independent and sustainable tourism industry ecosystem. The digitization of destinations in the Mandalika SEZ requires the hospitality industry to be able to adapt and respond strategically. The application of technology is believed to be applied in supporting the business continuity of the hospitality industry. This study aims to investigate the perceptions of hoteliers regarding technological adaptation. The method used is a phenomenological qualitative approach. Data were collected through observation, interviews with five key informants, and documentation. The interviews were transcribed and analyzed by condensing the data, assisted by a coding table. The results of this study found that two important aspects that drive the adoption of technology in hotel operational services are the desire for operational automation and marketing agility. The technology adoption process focuses on hotel operational services that are considered a necessity in the modern era and technological advancements. The existence of this technology adoption indicates the adaptability of technology in the hotel industry. This result contributes as a significant indicator of the progress towards digitalizing destinations, crucial for enhancing the sustainable image of Mandalika SEZ. Consequently, it is strongly recommended to develop an integrated technology application model for operational services, serving as a blueprint for other stakeholders in the hotel industry.